Oxidative Degradation of Methyl Ethyl Ketone by N-Chlorosaccharin - Khan, Shahnaz; Nigam, S.K.; Dwivedi, H.P.; Singh, P.K. (Asian Journal of Chemistry, 2016)
The oxidative feature of methyl ethyl ketone has been carried out with N-chlorosaccharin (NCSA) in aqueous acetic acid medium in presence of H+ ions. The dx/dt is a direct function of first power of concentration of oxidant (NCSA) and one to zero power of methyl ethyl ketone and acid. The reaction was found to decrease by the increasing concentration of reduction product saccharin and acetic acid. The reactive species H2O+Cl has been actively participated in 1 : 2 mole ratio with enolic ketone and exhibited complex nature of the reaction.